2017
DOI: 10.1038/cddis.2017.78
|View full text |Cite
|
Sign up to set email alerts
|

BBC3 in macrophages promoted pulmonary fibrosis development through inducing autophagy during silicosis

Abstract: Following inhalation into the lungs, silica particles are engulfed by alveolar macrophages, which triggers endogenous or exogenous apoptosis signaling pathways. As an inducer of apoptosis, the role of BBC3/PUMA (BCL2-binding component 3) in macrophages during silicosis remains unknown. Here, we exposed U937 cell-derived macrophages (UDMs) to SiO2 in vitro to explore the function of BBC3 in SiO2-induced disease. We found that SiO2 induced increased BBC3 expression, as well as macrophage activation and apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 57 publications
1
46
0
Order By: Relevance
“…Our previous study showed activated autophagy and increased autophagosomes in AMs of silicosis patients and mouse model [13,15]. Studies reported that inhibition of autophagy in macrophages could relieve CS-induced pulmonary fibrosis [58,59]. However, Atg5 knockdown in mice showed that impairment of autophagy aggravated CS-induced pulmonary inflammation and fibrosis [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed activated autophagy and increased autophagosomes in AMs of silicosis patients and mouse model [13,15]. Studies reported that inhibition of autophagy in macrophages could relieve CS-induced pulmonary fibrosis [58,59]. However, Atg5 knockdown in mice showed that impairment of autophagy aggravated CS-induced pulmonary inflammation and fibrosis [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…108 Rapamycin treatment has demonstrated antifibrotic abilities in murine bleomycin-mediated mortality and fibrosis 95,102 . However, rapamycin appears to enhance the effects induced by silicon dioxide 109 and IPF patients taking the rapamycin analog everolimus have progression of disease. 110 Again, further studies are required to evaluate the benefits of targeting autophagy in IPF and whether or not these targeting strategies should be cell type-specific.…”
Section: Interstitial Lung Disease Autophagy and Inflammationmentioning
confidence: 99%
“…Crystalline silica entering the airways is engulfed by macrophages, causing necrosis of the phagocytes, and then, the internalized silica is released again and engulfed by other macrophages. The repeated process of phagocytosis, necrosis and rephagocytosis of the cells induces in ammation and activation of the reactive oxygen species system, which is associated with pulmonary interstitial brosis [19,20]. Some metabolites in the pathogenesis of silicosis may play a predictive role in the diagnosis and severity of the disease.…”
Section: Discussionmentioning
confidence: 99%